Development and Demonstration of the Operational Sustainability Index (OPSi): A Multidimensional Metric for Building Performance Evaluation - Oluwafemi Awolesi; Margaret Reams (Buildings)
In promoting sustainable cities and societies, accelerating the shift from sustainable building design to sustainable building operations is essential. A persistent challenge lies in the absence of a unified, multidimensional metric that enables meaningful performance comparisons across buildings of similar types and functions, both regionally and globally. This study develops and demonstrates the operational sustainability index (OPSi)—a novel metric grounded in case study research that integrates indoor environmental quality (IEQ) and energy utility quality (EUQ). OPSi is applied to six buildings in three comparative cases: (1) LEED-certified and non-certified dormitories, (2) LEED-certified and non-certified event buildings, and (3) male- and female-occupied multifamily housing units. Results show that the LEED-certified dormitory underperformed in two of five OPSi variants compared to its non-certified counterpart despite achieving up to 18% higher objective IEQ performance. The LEED-certified event building outperformed its non-certified counterpart across all OPSi metrics, with up to 88% higher objective IEQ scores. Findings also include higher energy performance in male-occupied housing units than in female-occupied ones, highlighting behavioral differences worthy of future study. This research addresses longstanding criticisms of green certification systems—particularly their limited capacity to holistically measure post-certification operational performance—by offering a practical and scalable evaluation framework. OPSi aligns with global sustainability goals, including SDG 11 (Sustainable Cities and Communities) and SDG 7 (Affordable and Clean Energy), and supports smart, data-driven decision-making. Future applications may extend OPSi to include carbon life cycle assessment and maintenance metrics to further strengthen building sustainability in urban contexts.